Pengaruh Brand Ambassador Nct Dream Terhadap Keputusan Konsumen Pembelian Produk Mie Instan Lemonilo - Bariah, Habibah Salma; Anggriani, Salma Fadhilah; Azizah, Destia Ismayatun (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to ascertain how the NCT DREAM Brand Ambassador affects consumer choices regarding Lemonilo instant noodles in Karawang. In this kind of research, the causal relationship between variables is investigated using a simple linear regression. 100 respondents who had purchased or consumed Lemonilo instant noodles made up the sample for this study. A questionnaire was utilised to collect study data, and SPSS version 25 For Windows was employed for data analysis. According to the study's findings, NCT DREAM's role as a Brand Ambassador has a positive impact on consumers' decisions to buy Lemonilo instant noodles.